PARASOCIAL PIETY AND RELIGIOUS HARMONY: AUTHORITY AND MEDIA LITERACY IN INDONESIAN DIGITAL DAKWAH - Alan Munandar; Ari Santoso Widodo Poespodihardjo; Hillary Tasya Medina (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2026)
Indonesia's rapid digital expansion has transformed how Muslims access religious guidance, enabling digital preachers to build asymmetrical, emotionally significant bonds with millions of followers, a phenomenon this study conceptualizes as parasocial piety. In Indonesia's plural democratic society, where religious moderation (moderasi beragama) is a national policy priority, these parasocial dynamics carry consequential implications for social cohesion, interfaith discourse, and digital religious authority. This study explains the communicative mechanisms through which parasocial piety emerges in Indonesian digital dakwah, assesses its effects on religious moderation and social cohesion, and formulates an applied religious media literacy framework as an intervention response. Using an interpretive qualitative design with an integrative literature review, the article synthesizes peer-reviewed scholarship published mainly between 2021 and 2026, covering digital dakwah, parasocial interaction and relationship theory, Digital Islam, religious moderation, and digital religious literacy. Sources were selected through systematic screening following SALSA criteria, yielding a final corpus of 44 peer-reviewed journal articles. Findings identify five platform-conditioned mechanisms, including rhythmic presence, visual authority, and commodification of piety, that jointly produce mediated religious influence capable of both supporting and weakening religious moderation and inclusive discourse. The study contributes an original three-level ethical literacy framework for creators, audiences, and institutional ecosystems, with direct relevance to religious harmony policy in Indonesia's plural digital public sphere. Abstrak Ekspansi digital yang pesat di Indonesia telah mengubah cara umat Muslim mengakses bimbingan agama, memungkinkan dai digital membangun ikatan satu arah yang bermakna secara emosional dengan jutaan pengikut, fenomena yang dikonseptualisasikan dalam studi ini sebagai parasocial piety. Dalam masyarakat Indonesia yang plural dan demokratis, di mana moderasi beragama menjadi prioritas kebijakan nasional, dinamika parasosial ini membawa implikasi serius terhadap kohesi sosial, wacana lintas agama, dan otoritas keagamaan digital. Studi ini menjelaskan mekanisme komunikatif kemunculan parasocial piety dalam dakwah digital Indonesia, mengkaji dampaknya terhadap moderasi beragama dan kohesi sosial, serta merumuskan kerangka literasi media keagamaan terapan sebagai respons intervensi. Dengan desain kualitatif interpretatif dan integrative literature review, artikel ini mensintesis karya ilmiah peer-reviewed yang dipublikasikan dominan antara 2021 hingga 2026, mengenai dakwah digital, teori interaksi dan relasi parasosial, Digital Islam, moderasi beragama, dan literasi digital keagamaan. Sumber dipilih melalui penyaringan sistematis berdasarkan kriteria SALSA, sehingga menghasilkan korpus akhir sebanyak 44 artikel jurnal peer-reviewed. Temuan mengidentifikasi lima mekanisme berbasis platform, termasuk kehadiran ritmis, otoritas visual, dan komodifikasi kesalehan, yang secara bersama menghasilkan pengaruh keagamaan termediasi yang dapat sekaligus mendukung dan melemahkan moderasi beragama serta wacana inklusif. Studi ini berkontribusi melalui kerangka literasi etis tiga level bagi kreator, audiens, dan ekosistem institusional, dengan relevansi langsung terhadap kebijakan kerukunan beragama dalam ruang publik digital plural Indonesia.